Morphologic and morphometric analysis of glenoid cavity of human scapula - Raaj, Manisha S.; Felicia, Christilda; S., Sundarapandian; A., Ashma K. (International Journal of Research in Medical Sciences, 2018)
Background: To study the morphometry and morphology of glenoid cavity of dried scapula bone and in CT scan of glenoid cavity. The present study aimed at calculating three dimensions i.e. vertical diameter, horizontal diameter of the upper segment and horizontal diameter of the lower segment of the glenoid cavity and describing the incidence of its different shapes. Methods: This study was done on 100 dry, unpaired adult human scapulae of unknown sex. 50 scapulae belongs to right side and 50 scapulae belongs to left side obtained from Department of Anatomy, SRM Medical College and Research Institute. The above mentioned diameters are measured using Vernier caliper and the mean dimensions are calculated, morphological variations are studied. 3D CT images of scapulae, obtained from Department of Radiology, SRM Medical college and Hospital, Potheri, were also analysed. Results: In the current study, various dimensions and incidence of various shapes of glenoid cavity were measured. The incidence of both pear and inverted comma shape in right side is greater than in left whereas the incidence of oval shape in left side is greater than right side. The SI diameter of right glenoid is greater than the left, which is statistically significant. The Antero-posterior diameters (AP-1, AP-2, AP-3) of right glenoid is greater than the left, but not statistically significant. Conclusions: The knowledge of the above said variations of glenoid cavity is important in manufacturing the glenoid component of shoulder prosthesis, repair of Bankart’s lesion, procedures like posterior glenoid osteotomy.